Question
upstudy study bank question image url

substitution method: \[ 3 x+2 y=2 \text { and } 5 x-2 y=-18 \]

Ask by Murray Donnelly. in South Africa
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( x=-2 \) and \( y=4 \).

Solution

Solve the system of equations \( 3x+2y=2;5x-2y=-18 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3x+2y=2\\5x-2y=-18\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=\frac{2-2y}{3}\\5x-2y=-18\end{array}\right.\) - step2: Substitute the value of \(x:\) \(5\times \frac{2-2y}{3}-2y=-18\) - step3: Simplify: \(\frac{5\left(2-2y\right)}{3}-2y=-18\) - step4: Multiply both sides of the equation by LCD: \(\left(\frac{5\left(2-2y\right)}{3}-2y\right)\times 3=-18\times 3\) - step5: Simplify the equation: \(10-16y=-54\) - step6: Move the constant to the right side: \(-16y=-54-10\) - step7: Subtract the numbers: \(-16y=-64\) - step8: Change the signs: \(16y=64\) - step9: Divide both sides: \(\frac{16y}{16}=\frac{64}{16}\) - step10: Divide the numbers: \(y=4\) - step11: Substitute the value of \(y:\) \(x=\frac{2-2\times 4}{3}\) - step12: Calculate: \(x=-2\) - step13: Calculate: \(\left\{ \begin{array}{l}x=-2\\y=4\end{array}\right.\) - step14: Check the solution: \(\left\{ \begin{array}{l}x=-2\\y=4\end{array}\right.\) - step15: Rewrite: \(\left(x,y\right) = \left(-2,4\right)\) The solution to the system of equations \(3x+2y=2\) and \(5x-2y=-18\) is \(x=-2\) and \(y=4\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To use the substitution method, first solve one of the equations for one variable. Let's take the first equation: 1. Rearrange it to find \( y \): \[ 2y = 2 - 3x \] \[ y = 1 - \frac{3x}{2} \] 2. Now substitute \( y \) in the second equation: \[ 5x - 2(1 - \frac{3x}{2}) = -18 \] \[ 5x - 2 + 3x = -18 \] \[ 8x - 2 = -18 \] \[ 8x = -16 \] \[ x = -2 \] 3. Now substitute \( x \) back into the expression for \( y \): \[ y = 1 - \frac{3(-2)}{2} \] \[ y = 1 + 3 = 4 \] So the solution to the system of equations is \( x = -2 \) and \( y = 4 \). Want to know how to graphically represent this solution? Just plot both equations on the same graph, and you'll see they intersect at the point (-2, 4)!

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy